Hubungan Asupan Lemak dan Status Gizi Dengan Siklus Menstruasi pada Siswi SMA N Colomadu - Novitasari, Ika; , Ririn Yuliati S.Si.T., M.Si; , Luluk Ria Rakhma , S.Gz., M.Gizi (2016)
Introduction: The nutrient intake and nutritional status can affect the menstrual cycle, imbalance nutrient intake and nutritional status will affect the growth and function of organs which leads to disruption of reproductive function and disturb the menstrual cycle. Objective: To determine the relationship of fat intake and nutritional status to the menstrual cycle among female students The Colomadu State High School. Research Methods: This research is observational study with cross-sectional design. Total subjects were 61 female students, who were selected through systemic proportional random sampling of all female students in class XI who had qualification of inclution and exlution criterias. Nutrient intake (fat) data were obtained using from SQ-FFQ (Semi Quantitative Food Frequency Questionaires), nutritional status data were obtained by measuring the weight and height which then determine the z-score of BMI for age, while menstrual cycle data were obtained from the questionaire. Data were analyzed using Pearson Product Moment test. Results: A total of 32 (52.5%) of the subjects experienced abnormal menstrual cycles. Most subjects have high levels of fat intake more than the RDA is 25 (41.0%). A total of 49 subjects, (80.3%) had good nutritional status. Statistic test showed that there is a relationship of fat intake to menstrual cycle (p=0.012;r=0.312) and nutritional status to menstrual cycle (p=0.028;r=0.281). Conclusion: There is relationship of fat intake and nutritional status to the menstrual cycle among adolescent female students The Colomadu State High School.